Hepatobiliary Cystadenomas and Cystadenocarcinoma. Report of Five Cases - Gadijev, E. (Hindawi Publishing Corporation, 1996)
Clinicopathologic correlation offive cases ofcystadenomas of the liver are reported. All patients were female and radical surgical procedure, total excision or resection was performed four times, and partial excision once. In all patients the postoperative course was uneventful and they are all alive and well. Examined by conventional histological and special immuno-histochemical stains the tumors fulfilled diagnostic criteria for these rare cystic growths. The cyst wall was composed of three, histologically distinct layers. From the viewpoint of histogenesis and differential diagnosis immunohistochemical properties were analysed. CEA and EMA were demonstrated in epithelial cells and Vimentin in stromal cells.